สัณฐานวิทยาของผลึกซิลเวอร์อะซิเตทซึ่งสังเคราะห์จากโลหะเงินโดยตรง - มณิสร สุขสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Silver acetate (AcOAg) was employed as a raw material in many applications such as health products, medical devices, silver coatings and conductive silver inks. In general, silver nitrate (AgNO₃) is a precursor for synthesizing AcOAg. However, the production of AgNO₃ produces nitrogen oxide (NOx), a family of toxic gases that severely affect the environment and human health. In this research, we prepared flower-like AcOAg directly from silver metal in organic solvents. By immersing ~2 mm silver metal in a solution containing ethyl acetate (AcOEt), acetic acid (AcOH), and hydrogen peroxide (H₂O₂). The silver metals were formed into AcOAg within 24 h. AcOAg crystals slowly develop and assemble into bundles around the silver metal. The morphology of the AcOAg was investigated by optical microscope and scanning electron microscope. Characterization of synthesized AcOAg by Raman Spectroscopy, Fourier transform infrared spectroscopy and X-Ray diffraction spectroscopy was carried out. The developed process is environmental friendly, energy efficient, one-pot, simple while emitting no chemical waste or toxic by-products.